THE ABILITY OF SELF-CONTROL IN INFLUENCING THE EMERGENCE OF AGGRESSIVE BEHAVIOR IN ADOLESCENTS - Hidayat, Rahmat; Maula Akbar, Septian; Rokhman, Abdul; Saifudin, Moh. (Journal of Vocational Nursing, 2025)
Introduction: Adolescence is a transitional period between childhood and adulthood, characterized by social and psychological changes, making teenagers vulnerable to aggressive behavior. Aggressive behavior in adolescence has become a serious issue because it can have negative impacts, such as being labeled a troublemaker or being shunned by peers. The purpose of this study was to examine the relationship between self-control and aggressive behavior in adolescents. Methods: This study used a correlational design with a cross-sectional method. The population consisted of 194 adolescents, from which a sample of 129 participants was selected using the simple random sampling technique. Self-control was measured using a questionnaire consisting of 17 items, including 9 favorable and 8 unfavorable items, with a Cronbach’s alpha reliability coefficient of 0.825. Aggressive behavior was measured using 32 items, including 30 favorable and 2 unfavorable items, with a Cronbach’s alpha of 0.806. After data tabulation, analysis was performed using Spearman’s rho test with SPSS. Results: There was a significant negative correlation between self-control and aggressive behavior in adolescents (rs = -0.559, p < 0.001). Conclusions: These results indicate that adolescents with higher self-control tend to exhibit lower levels of aggressive behavior. Efforts to reduce aggression can be made by enhancing self-control through the development of emotional maturity in adolescents.